Строговы: роман / Г. М. Марков - Марков Георгий Мокеевич (Сибириада. Собрание сочинений, 2013)
Экземпляры: СБ (201503) / Инвентарный номер: 50630 / Цена: 226.10 / Сис.шифр: Р2 / Авт.знак: М 27 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6